SARIMA(X) AND DECISION TREE MODELS COMPARISON FOR LOAD FORECASTING IN ELECTRICAL GRIDS - Кирик, Валерій; Шаталов, Євген (Modern engineering and innovative technologies, 2024)
This work compares load forecasting models in the electrical network based on SARIMA(X) and Decision Tree. Various versions of the above models were trained on load data for 2021 for one of the substations in the Kyiv region. The day 01/01/2022 was select